The Matter of Grandma Minah in the Perspective of Positivism - YAPRIZAL, Andi; THEOPILUS, Ebith; KRISTHY, Mutia Evi (Journal of Political And Legal Sovereignty, 2023)
Purpose: In a law there are various parties who will enforce the laws in force in Indonesia. These parties carry out law enforcement so as not to create a violation of the law, bring order to society and regulate society in accordance with the norms and rules that apply in a country is not easy to apply in public life.Methodology:The resolution of a case of violation of the law is a legal process. Legal process is an action to resolve cases of violations of the law to achieve a settlement in accordance with applicable regulations in Indonesia.Findings: In legal cases that have occurred in Indonesia, the provision of criminal sanctions against Grandma Minah who is a cocoa thief has received a lot of attention from the public. The case of "Grandma Minah" is an example of law enforcement in Indonesia that is still considered by the public to have not realized sanctions in rulings in accordance with conscience and moral considerations.Implication:The reason that often arises is the injustice of sanctions against theft crimes that can actually still be resolved by familial means. But this is the reality that occurs on the ground between legal theory and practice that has different implementations.